TRANSPORT KOMPANIYASINING MODDIY TA’MINOTINI BOSHQARISH - Solimuhammadov Jamshidbek Sohibjon o’g'li; Mamajonova Muxlisaxon O‘ktamjon qizi; Hoshimov O‘tkirbek Hakimjon o‘g‘li (Лучшие интеллектуальные исследования, 2024)
ANNOTATION: The article discusses the responsibilities of the logistics service at motor transport enterprises. Planning of spare parts and materials according to criteria. Providing fuel and energy resources to motor transport enterprises. You can also take the following steps to manage the logistics of a transport company: